The Effectiveness of Problem-Based Learning on Ecosystem Content toward Critical Thinking in Terms of Students' Metacognitive Awareness - Wiono, Wisnu Juli; Siregar, Yessica Solafide (Phenomenon : Jurnal Pendidikan MIPA, 2024)
This research aims to determine the effect of applying the PBL model on students' critical thinking abilities and to describe students' critical thinking abilities on the interaction of living things and their environment in terms of metacognitive awareness. The design in this research is a quasi-experiment using the Pretest-Posttest Control Group Design technique. Samples were taken using purposive sampling technique. Metacognitive awareness data was obtained through the Metacognitive Awareness Inventory (MAI) questionnaire which was analyzed descriptively. The population of this research was class VII students at SMPN 43 Bandar Lampung with a sample of 27 class VII 1 students as the experimental class and 25 class VII 2 students as the control class. The average N-Gain value for the experimental class was 0.65, the "medium" criterion. The N-Gain homogeneity test is Sig.0.250> 0.05. Test the hypothesis with the Sig value. (2-tailed) 0.00 < 0.05. The effect size test result was 1.18 with the criteria "large". Based on these results, it shows that the use of the PBL model is effective in improving students' critical thinking skills on the interaction of living things and their environment. The results of the analysis between metacognitive awareness and critical thinking skills descriptively show that more than half of the students who are at the 'developed' metacognition level consist of students who are in the medium and high critical thinking categories.